Viability Reagent, PrestoBlue, in Comparison with Other Available Reagents, Utilized in Cytotoxicity and Antimicrobial Assays - Namrita Lall; Cynthia Joan Henley-Smith; Marco Nuno De Canha; Carel Basson Oosthuizen; Danielle Berrington (International Journal of Microbiology, 2013)
This study compared different commercially available viability reagents. The growth indicator reagents include p-iodonitrotetrazolium violet (INT), PrestoBlue, and Alamar Blue which were used for antimicrobial analysis against Streptococcus mutans, Prevotella intermedia, Propionibacterium acnes, and Mycobacterium tuberculosis. PrestoBlue and Alamar Blue are resazurin based reagents that resulted in a quick and easily distinguishable colour change that allowed for visual readings. INT and Sodium 3′-[1-(phenyl amino-carbonyl)-3,4-tetrazolium]-bis-[4-methoxy-6-nitro] benzene sulfonic acid hydrate (XTT) are tetrazolium based reagents which are converted to a formazan dye in the presence of metabolically active mitochondria enzyme. For cell viability analysis, reagents XTT and PrestoBlue were compared. PrestoBlue was able to clearly indicate the minimum inhibitory concentration (MIC) of various positive drug controls on various microbial strains. PrestoBlue was also a good indicator of the 50% inhibitory concentration (IC50) of positive drug controls on various cell lines.